Factors Affecting the Performance of Small Micro Medium Enterprise (UMKM) in Lagoa Village - Robiur Rahmat Putra; Siti Holisoh (PT Mattawang Mediatama Solution, 2023)
UMKM is a productive economic efforts controlled by individuals, or agencies but with special business capital and limitations in increasing efforts, and not alliances that belong to companies or cooperatives UMKM b ecomes one of the important economy pillars in Indonesia when there was a monetary emergency in 1997. When many large industries went bankrupt in that era, UMKM activities in Indonesia even increased when companies/industries experienced in a bad situation. This research aims to find out the factors affecting performance of Small Micro Medium Enterprise (UMKM). Research used quantitative methods which conducted at the Lagon MMS, Jakarta. Sampling technique used probability sampling with simple random sampling techniques of 97 respondents. Data analysis techniques employed Smart PLS3 software. The results show that the factors affecting performance of UMKM namely knowledge, business capital, information systems, E-commerce, and environmental uncertainty affecting knowledge.